Absent from the pages of history (the Karbala incident) (Journal of the College of Basic Education, 2025)
Omission from history is one of the challenges facing historians and intellectuals in their attempts to present a comprehensive and accurate historical narrative that shows all the parts and positions. It may be intentional by a certain group that had control at a certain time, or unintentional due to lack of information. Due to the importance of all individuals involved in the Karbala incident, the research included three topics: The first topic: We addressed the linguistic and technical aspects of absentations . In the second topic: We addressed the Karbala incident between the present and the past. In the third topic: The subject of those absent in the Karbala incident came.